2001
DOI: 10.1359/jbmr.2001.16.6.975
|View full text |Cite
|
Sign up to set email alerts
|

Osteoblast Apoptosis and Bone Turnover

Abstract: With the discoveries of different death mechanisms, an emerging definition of apoptosis is the process of cell death associated with caspase activation or caspase-mediated cell death. This definition accepts that caspases represent the final common mechanistic pathway in apoptosis. Apoptosis may be triggered either by activation events that target mitochondria or endoplasmic reticulum or by activation of cell surface "death receptors," for example, those in the tumor necrosis factor (TNF) superfamily. In the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
123
1
8

Year Published

2001
2001
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 216 publications
(138 citation statements)
references
References 111 publications
(141 reference statements)
6
123
1
8
Order By: Relevance
“…In contrast to published reports indicating that pharmacological concentrations of glucocorticoids increase OB and OCY apoptosis [Manolagas, 2000;Hock et al, 2001;Boyce et al, 2002], treatment of HOB cells representing pre-OBs and mature-OBs with Dex downregulated sFRP-1 mRNA levels and inhibited PCD. Other studies have also reported that Dex treatment suppresses OB apoptosis in vitro [Zalavras et al, 2003].…”
Section: Discussioncontrasting
confidence: 85%
See 2 more Smart Citations
“…In contrast to published reports indicating that pharmacological concentrations of glucocorticoids increase OB and OCY apoptosis [Manolagas, 2000;Hock et al, 2001;Boyce et al, 2002], treatment of HOB cells representing pre-OBs and mature-OBs with Dex downregulated sFRP-1 mRNA levels and inhibited PCD. Other studies have also reported that Dex treatment suppresses OB apoptosis in vitro [Zalavras et al, 2003].…”
Section: Discussioncontrasting
confidence: 85%
“…Finally, although estrogens and PTH have been reported to decrease OB and OCY apoptosis [Manolagas, 2000;Hock et al, 2001;Boyce et al, 2002], treatment of the HOB cells with these hormones did not affect sFRP-1 gene expression or cell viability.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…(15) Many studies have provided evidence for TNF-a's apoptotic action in osteoblasts. (33)(34)(35) TNF-a also can augment apoptotic stimuli that are induced by Fas ligand or cycloheximide. (36) In osteoblastic cells, TNF-a's main apoptotic effects are mediated by tumor necrosis factor receptor 1 (TNFR1) and lead to the recruitment of TNFR1-associated death domain, which serves as a platform for generating various signaling complexes.…”
Section: Discussionmentioning
confidence: 99%
“…1 A balance among proliferation, differentiation, and apoptosis determines the population size of osteoblasts in the skeleton. 2 A variety of systemic and local factors are involved in the regulation of osteoblast activities. 3 Nitric oxide (NO), synthesized from L-arginine by NO synthases, has been shown to be one such factor.…”
Section: Introductionmentioning
confidence: 99%